Human Psittacosis: A Case Report - Cipriano, Ana (2019)
Psittacosis is a rare disease caused by Chlamydophila psittaci, an intracellular bacteria transmitted by contaminated birds. The clinical and radiological presentations are nonspecific. We describe a case of a 42-year-old woman, with known exposure to birds, who presented to the emergency department with one-week evolution of myalgia, polyarthritis, and respiratory symptoms. At admission, she had fever, respiratory failure, raised inflammatory markers and bilateral interstitial infiltrates at chest radiography. Considering the clinical findings and epidemiological background, we raised the hypothesis of a Chlamydophila psittaci atypical pneumonia that was serologically confirmed. Tetracyclines are the mainstay of treatment and the macrolides are an effective alternative. We highlight the importance of the epidemiological context in the early diagnosis and treatment of this infection.